Illocutionary Speech Act Translation in Gala Bunga Matahari Song Lyrics: A Pragmatic Equivalence Analysis - Mukminin, Muhamad Saiful (Centre for Literary and Cultural Studies, 2025)
The present study analyzes the pragmatic equivalence in the translation of illocutionary speech acts in the lyrics of Gala Bunga Matahari by Sal Priadi. Using a descriptive qualitative approach, this research examines how illocutionary speech acts in the source language (Indonesian) are maintained or altered in the target language (English). Data consist of speech units in the song lyrics and their translations obtained from YouTube’s auto-translate feature, categorized into representative, directive, expressive, commissive, and declarative acts. Data collection follows the documentation method, and analysis is conducted using interactive model: data reduction, data presentation, and conclusion drawing. Findings reveal that most speech acts maintain pragmatic equivalence, especially in assertives, directives, commissives, and expressives. However, shifts occur, such as directives changing into commissives and vice versa, altering communicative intent. Some non-equivalence arises due to grammatical differences and translation adjustments for naturalness in English. Despite these shifts, the translation largely preserves the song’s core message. This study highlights the complexities of translating song lyrics while maintaining illocutionary intent, contributing to research in translation studies and pragmatics.